2016
DOI: 10.1016/j.jadohealth.2015.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Disability and the Context of Boys' First Sexual Intercourse

Abstract: Boys with and without disabilities-and boys with different types of disabilities-vary significantly in multiple aspects of their first sexual experiences. It is pertinent that sexual health interventions are tailored to address this diversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
0
11
1
Order By: Relevance
“…When comparing confidence intervals, we also found females with moderate disabilities had a slower progression to vaginal sex and first sexual experience compared to females without disabilities. These moderation results conflict with past longitudinal research by Shandra and colleagues (4,5), who found males with disabilities differed from those without disabilities, but females with disabilities were no different from females without disabilities. Such conflicting results may be due to differences in the items used to assess sexual experiences.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…When comparing confidence intervals, we also found females with moderate disabilities had a slower progression to vaginal sex and first sexual experience compared to females without disabilities. These moderation results conflict with past longitudinal research by Shandra and colleagues (4,5), who found males with disabilities differed from those without disabilities, but females with disabilities were no different from females without disabilities. Such conflicting results may be due to differences in the items used to assess sexual experiences.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, studies indicate that women engage earlier in vaginal intercourse (7), while men experience oral and anal sex earlier (1). Among populations with disabilities, Shandra and colleagues (4) found males with learning or emotional conditions were more likely, and those with sensory conditions were less likely, to report earlier sexual debut than males without disabilities. In a similar paper, Shandra and Chowdhury (5) found no differences in mean age at first sex for females.…”
Section: Introductionmentioning
confidence: 99%
“…911 For instance, in their cross-sectional study of 14–17 year olds in Germany, Wienholz and colleagues 11 found that a smaller proportion of teens with physical disabilities and vision or hearing impairments reported experiencing vaginal intercourse than did those without disabilities; however, among sexually experienced teens with disabilities, males and those with hearing impairments were more likely to have reported ever having vaginal intercourse. In contrast, using data from the National Longitudinal Study of Youth (NLSY), Shandra and colleagues 10 found that sexually experienced males with sensory conditions were less likely to report earlier sexual debut compared to males without any type of disability. However those with learning or emotional conditions were more likely to report early sex.…”
Section: Introductionmentioning
confidence: 95%
“…Disability overlaps with other social statuses such as sexual orientation [21], and this intersectionality has the potential to expand knowledge about service delivery and health equity [22]. Second, the authors suggest that the patterns observed in the longer exposure window of their study-versus previous analyses of sexual behavior and disability [2,3,23,24]-are indicative of changes in sexual behavior over time. Childhood disability may impact life course transitions differently depending on age of onset and type of disability [25]; a comprehensive longitudinal analysis of people with disabilities' relationship trajectories between adolescence and early adulthood can unpack the patterns observed in the 14-year window captured here.…”
mentioning
confidence: 93%
“…One in four children experience disability by young adulthood [1]. During adolescence, they have sexual intercourse, report varying types of relationships with their sexual partners, and experience divergent degrees of discussion about family planning with those partners [2,3]. As they age, they get married and become parents [4,5].…”
mentioning
confidence: 99%